Estudo comparativo entre sevofluorano, halotano e isofluorano em Gallus domesticus - Guimarães, Luciana Dambrosio; Moraes, Aury Nunes de; Campello, Rui Afonso Vieira; Oleskovicz, Nilson [UNESP]; Ulliana, Daiana (Universidade Federal de Santa Maria (UFSM), 2000)
Foram utilizados 30 frangos com 20 semanas de idade, pesando em média 2,90 ± 0,65kg divididos aleatoriamente em três grupos. A indução da anestesia foi realizada com máscara facial artesanal conectada ao sistema de Maggil Modificado, utilizando entre 3,0 e 3,5 vezes a dose anestésica mínima (DAM) de cada agente e fluxo diluente de O2 de 2l/min, sendo que posteriormente os animais foram intubados e mantidos com valores de aproximadamente 1,7DAM durante 65 minutos. O isofluorano causou maior depressão respiratória e hipotensão; o halotano proporcionou maiores valores de pressão arterial e temperatura corporal e o sevofluorano, menor depressão respiratória e hipotensão em relação ao grupo do isofluorano, sendo considerado o agente mais indicado para a utilização em aves. A indução e recuperação foram mais rápidas com o sevofluorano, embora sem diferença significativa estatisticamente.

For the comparison 30 twenty-week-old chicken were used. They weigh na averdage of 2.90 ± 0.65kg aleatorily divided into 3 groups. The anesthetic induction was accomplished with a home-made facial mask connected with the modified circuit of Maggil using values between 3.0 e 3.5 a minimal anesthetic dose (MAD) for each agent. Posteriorly, the animals were intubated and anesthesia was maintained with values approximately 1.7DAM during 65 minutes. Isoflurane caused further respiratory depression and hypotension when it is compared to the other two anesthetic agents. The group of halothane presented higher values of blood pressure and body temperature and the group of sevoflurane, lower respiratory depression and hypotension in relation to the group of isoflurane. The induction and recuperation were faster with the sevoflurane, although without expressive diference statistically. The sevoflurane is the most indicated anesthetic agent.
Comparite evaluation with sevoflurane, halothane and isoflurane in Gallus domesticus
Keywords: anestesia inalatória; aves; monitoração; inhalant anesthesia; birds; monitoration